Morfometria e compactação da cromatina espermática de touros Nelore de acordo com a idade e sua influência na produção de embriões in vitro - Kipper, Bruna Helena [UNESP] (2014)
The aim of this study was to evaluate chromatin condensation and sperm head morphometry of cryopreserved semen samples from Bos taurus indicus bulls of different ages and the influence of the degree of chromatin condensation on in vitro embryo production (IVP). A total of 40 animals kept in an Artificial Insemination Centre were divided into three groups: Young Group (1.8 to 2 years), Adult Group (3.5 to 7 years) and Senile Group (8 to 14.3 years). The ejaculates were frozen in accordance with established standards of the Artificial Insemination Centre. The thawed semen samples were evaluated with toluidine blue, which analyzes the chromatin condensation and sperm head morphometry simultaneosly, chromomicin A3 (CMA3) to analyze the protamination and in vitro embryo production to analyze the embryonic development. The toluidine blue was evaluated by optical microscopy and the CMA3 by flow cytometry. Semen analyses revealed that spermatozoa of young bulls had higher values of area (A), perimeter (P) and width (W) when compared to adults and senile (Young: A = 1848.5 ± 119.79, P = 10. 23 ± 0.29, W = 1.95 ± 0.1; Adults: A = 1672.9 ± 104.46, P = 9.86 ± 0.33, W = 1.81 ± 0.06; Senile: A = 1723.1 ± 124.41, P = 9.97 ± 0.33, W = 1.83 ± 0.09; P<0.0001) and had higher protamination deficiency when analyzed with CMA3 (Young: 1.57 ± 0.76, Adults: 1.09 ± 0.63, Senile: 0.90 ± 0.59, P<0.05). Variable size (A, P, W) and sperm protamination evaluated by CMA3 showed negative correlation with age and a positive with ellipticity (P<0.05). Spermatozoa with abnormal chromatin obtained larger area when compared to those with normal chromatin (P<0.0001). There was no significant difference in IVP using semen with higher and lower altered chromatin condensation, evidencing that the proportion of spermatozoa with abnormal chromatin (4 to 16.15%) did not affect the embryonic development. Our results indicate that sperm head of young bulls are ...